Intestinal Stem Cell Niche: The Extracellular Matrix and Cellular Components - Laween Meran; Anna Baulies; Vivian S. W. Li (Stem Cells International)
The intestinal epithelium comprises a monolayer of polarised columnar cells organised along the crypt-villus axis. Intestinal stem cells reside at the base of crypts and are constantly nourished by their surrounding niche for maintenance, self-renewal, and differentiation. The cellular microenvironment including the adjacent Paneth cells, stromal cells, smooth muscle cells, and neural cells as well as the extracellular matrix together constitute the intestinal stem cell niche. A dynamic regulatory network exists among the epithelium, stromal cells, and the matrix via complex signal transduction to maintain tissue homeostasis. Dysregulation of these biological or mechanical signals could potentially lead to intestinal injury and disease. In this review, we discuss the role of different intestinal stem cell niche components and dissect the interaction between dynamic matrix factors and regulatory signalling during intestinal stem cell homeostasis.